Bioenergetic Pathways in the Sperm of an Under-Ice Spawning Fish, Burbot (Lota lota): The Role of Mitochondrial Respiration in a Varying Thermal Environment - Rahi, Deepali; Dzyuba, Borys; Policar, Tomas; Malinovskyi, Oleksandr; Rodina, Marek; Dzyuba, Viktoriya (Biology, 2021)
Regarding the sperm of cold-water fish, the contributions of different bioenergetic pathways, including mitochondrial respiration, to energy production at the spawning temperature and its adaptation at the maximum critical temperature (CTmax) are unclear. The roles of glycolysis, fatty acid oxidation, oxidative phosphorylation (OXPHOS) at 4 °C, and OXPHOS at 15 °C for energy production in burbot (Lota lota) spermatozoa were studied by motility and the oxygen consumption rate (OCR) (with and without pathway inhibitors and the OXPHOS uncoupler). At both temperatures, the effects of the inhibitors and the uncoupler on the motility duration, curvilinear velocity, and track linearity were insignificant; in addition, the OCRs in activation and non-activation media differed insignificantly and were not enhanced after uncoupler treatment. After inhibitor treatment in both media, OXPHOS was insignificantly different at the 2, 30, and 60 s time points at 4 °C but was reduced significantly at the 30 and 60 s time points after treatment with sodium azide at 15 °C. In conclusion, for burbot sperm at both the spawning temperature and the CTmax, the energy synthesized via OXPHOS during motility was insufficient. Therefore, the majority of the energy required to sustain motility was derived from pre-accumulated energy produced and stored during the quiescent state of the spermatozoa.
Keywords: cold-water fish; oxidative phosphorylation; maximum critical temperature; sperm motility; glycolysis; spawning temperature; fatty acid oxidation